2017
DOI: 10.1007/s12571-017-0707-x
|View full text |Cite
|
Sign up to set email alerts
|

Zero-tillage is a proven technology for sustainable wheat intensification in the Eastern Indo-Gangetic Plains: what determines farmer awareness and adoption?

Abstract: In India, there is increasing recognition among policy-makers of the largely untapped potential of the Eastern Indo-Gangetic Plains (IGP) for meeting state-and national-level food needs. Zero-tillage (ZT) is a proven technology for enhancing wheat productivity and, hence, food security in the IGP, while reducing production costs -a 'win-win' scenario that should support rapid technology scaling even though adoption remains modest to date. In order to inform policies and derive recommendations for a more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 28 publications
(81 reference statements)
0
42
0
Order By: Relevance
“…In the Eastern IGP in particular, the above-mentioned small landholding sizes complicate the uptake of the technology as tractor and ZT drill ownership is not a tenable goal for the large majority of farmers; hence, they rely on custom-hiring services to access the technology (Erenstein and Laxmi, 2008, Keil et al, 2016). Furthermore, compared with the Northwestern IGP, farmers’ awareness of the technology is still low (Keil et al, 2017, Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Eastern IGP in particular, the above-mentioned small landholding sizes complicate the uptake of the technology as tractor and ZT drill ownership is not a tenable goal for the large majority of farmers; hence, they rely on custom-hiring services to access the technology (Erenstein and Laxmi, 2008, Keil et al, 2016). Furthermore, compared with the Northwestern IGP, farmers’ awareness of the technology is still low (Keil et al, 2017, Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Taking these factors into account, Keil et al (2017) assessed determinants of ZT wheat adoption in Bihar using cross-sectional data collected in 2013 and found a distinct scale bias, with larger, better educated, and higher-caste farmers being more likely to know about and use the technology. This is in line with the critique of SI initiatives articulated by Rasmussen et al (2018): in their recent review of literature evaluating 60 cases of agricultural intensification, the authors found that well-being impacts tended to be unevenly distributed, favoring better-off farmers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation agriculture utilizes three basic principles -no or reduced tillage, permanent ground cover and judicious crop rotation [6,7]. With the advent of zero till wheat, mechanized dry seeding of rice, increasing market availability of herbicides and rising concern over soil degradation, CA systems have gained increased attention in recent decades in the Indo-Gangetic Plain (IGP) of South Asia [6][7][8]. The use of CA in the rice-wheat (R-W) cropping systems of the IGP has been the subject of much research, and has been shown to maintain or increase crop yields, increase profitability, and improve soil fertility [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta-analysis of large set of global data demonstrated that yields with zero tillage but without residue retention are lower than conventional tillage especially in the humid tropics [12]. Nevertheless, in contrast to sub-Saharan Africa where CA and conservation tillage practices have been found to be more labour intensive [13], such technologies may hold potential to tackle labour and energy shortage in agriculture in Bangladesh and in the EGP [14,11,8].…”
Section: Introductionmentioning
confidence: 99%